Antiferromagnetism of β-Ce under hydrostatic pressure. (June 2019) - Malavi, Pallavi; Deng, Yuhang; Guillou, Francois; Mudryk, Yaroslav; Pecharsky, Vitalij; Schilling, James S.
Abstract: The magnetic properties of β-Ce at low temperature have been studied through ac susceptibility measurements under hydrostatic He-gas pressure up to 4.5 kbar. The Néel temperature, T N = 12.7 K at 58 bar, initially increases with pressure at the rate dT N / dP = +0.32 ± 0.05 K/kbar. After releasing pressure from 4.5 to 0.06 kbar at 40 K, the magnetic susceptibility anomaly associated with the antiferromagnetic transition is markedly reduced. Surprisingly, T N also shifts from 12.7 to 14 K. Both effects likely arise from an irreversible β → α transition under pressure. Highlights: Néel temperature of beta-Ce increases under hydrostatic pressure. Application of hydrostatic pressure at 25–40 K generates an irreversible conversion of beta-Ce to alpha-Ce. In mixed phase β-/α-Ce the α-Ce component exerts lattice pressure on the β-component, thereby increasing the Néel temperature.